Wideband patch directional coupler based on non‐uniform mushroom structure. Issue 3 (1st February 2015) - Zhou, Xin Yu; Zheng, Shao Yong; Pu, Xing Yu; Chan, Wing Shing; Long, Yunliang
Abstract : A wideband patch directional coupler is proposed. The coupler is designed based on the non‐uniform mushroom structure with unique characteristics. The current distribution within the patch can be controlled by the mushroom cells underneath for wideband property. An 8 dB directional coupler has been designed, fabricated and measured for verification. It exhibits good return loss, small coupling coefficient variation and quadrature phase difference among the output ports over a wide bandwidth of 74.6% centred at 8.45 GHz.